PENGEMBANGAN KOMIK BIOLOGI BERBASIS WEB SEBAGAI PERANGKAT BAHAN AJAR MATERI VIRUS KELAS X MA MUHAMMADIYAH PURBOLINGGO - Desmita Tyas Suryati; Agus Sujarwanta; Handoko Santoso (EDUBIOLOCK, 2025)
This research aims to develop innovative learning media in the form of web-based comics on biological material, especially about viruses. The background to this research is the low reading interest and learning motivation of students towards conventional biology textbooks. This research uses a 4D model (Analysis, Design, Development, Desiminate). The research participants consisted of class X students at one of the MA Muhammadiyah Purbolinggo. Data was collected through questionnaires, observations and interviews, and analyzed using quantitative and qualitative descriptive techniques. This testing is carried out by validating the media with material, language, design and student expert validators. The research results show that web-based comics have test scores above 80%, which means they are very suitable to be used as learning media so they are effective in increasing students' reading interest, learning motivation and understanding of biology material.